Mathematics - Mechanics and Probability - Bostock L.; Chandler S (Stanley Thornes (Publishers) Ltd, 1984)
This book is about Mechanics and the solving of mechanical problems with the help of Pure Mathematics. Preface, Introduction, Vectors. Components and Resultants. Moment, Coplanar Forces in Equilibrium. Friction, Velocity and Acceleration, Newton's Laws of Motion, Work and Power, Momentum. Direct Impact, Projectiles, Motion in a Circle, General Motion of a Particle, Simple Harmonic Motion, Resultant Motion. Relative Motion, Resultants of Coplanar Forces. Equivalent Force Systems, Centre of Gravity, Problems Involving Rigid Bodies, Frameworks, Probability, Appendix, Answers, Index.